TINJAUAN SISTEMATIS TENTANG PENERAPAN PRINSIP ETIKA BISNIS PADA UMKM DI DIGITALISASI - Miftahqul Mauliddia Rokhmawati; Ach Fariz Surya Ramadhan; Adi Lukman Hakim; nuning nurna dewi (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2026)
This research aims to understand the implementation of business ethics in MSMEs in the era of globalization. Micro, Small, and Medium Enterprises (MSMEs) play an important role in every country, including Indonesia, as they drive the economy and contribute to national development in this era of globalization. Based on the research results, many business actors still lack the implementation of business ethics such as honesty, fairness, and responsibility when selling products directly. This study identifies